THE ROLE OF DIGITAL HR TRANSFORMATION, WORKLOAD, AND EMPLOYEE READINESS ON GOAL ACHIEVEMENT AT PT MALINDO FEEDMILL LAMPUNG - Asih Triranti; Euis Mufahamah; Harold Kevin (International Journal of Management, Economic and Accounting, 2026)
The rapid development of digital technology in the Industrial Revolution 4.0 era demands organizations to adapt, particularly in human resource management. This study aims to analyze the effect of Digital Human Resource (HR) Transformation, Workload, and Employee Readiness on Goal Achievement at PT Malindo Feedmill Lampung. This research employs a quantitative explanatory design. The population in this study was 117 employees of PT Malindo Feedmill Lampung. The sampling method utilized was saturated sampling (census), resulting in a sample of 117 respondents. Primary data was collected through questionnaires measured using a Likert scale and analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) via SmartPLS software. The results of the structural model evaluation indicate that the independent variables simultaneously account for 85.0% of the variance in Goal Achievement. Partially, the hypothesis testing reveals that while Digital HR Transformation has a positive direction, it does not significantly affect Goal Achievement directly. Conversely, Workload and Employee Readiness both have a positive and highly significant impact on Goal Achievement. It can be concluded that organizational targets cannot be achieved solely by implementing digital systems; it requires a strong synergy between the adoption of technology, effective and balanced workload management, and the mental and technical readiness of the employees.